Characteristics of SKD 61 and Aluminium 7075 Tools in High Density Polyethylene (HDPE) and Polypropylene (PP) Welding in Terms of Tensile Strength and Bending strength - Alkafi, Abu Faqih; Darsono, Febri Budi; Kriswanto; Rochim, Mohammad Nur (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
Effective welding procedures are necessary to preserve structural integrity due to the growing usage of lightweight polymers in industry, such as polypropylene (PP) and high density polyethylene (HDPE). This study sought to determine how the tool materials, SKD 61 and Aluminum 7075, affected the tensile and bending strength of HDPE and PP friction stir welded (FSW) joints. A quantitative comparative design was used in the experiment, and the FSW tool was modified milling equipment with screw cylindrical pin tools. Temperature control was observed using a thermogun and no preheating was used to guarantee process stability. Based on the results, SKD 61 generated higher weld quality, which was characterized by fewer flaws, regulated heat input, and more consistent material flow. SKD 61 outperformed than aluminium 7075, which had an average tensile strength of 11.09 MPa and bending strength of 19.11 MPa, while aluminium 7075 had an average tensile strength of 7.8 MPa and bending strengths of 16.28 MPa. This discrepancy is explained by SKD 61's higher heat conductivity and stability, whereas tool geometry had little effect because the screw cylindrical pin profile was the same. SKD 61 is more suited for FSW of HDPE-PP dissimilar joints, according to the study's findings, offering higher joint quality and stronger mechanical performance.